Case Report: Immune-mediated Complete Response in a Patient With Recurrent Advanced Ewing Sarcoma (EWS) After Vigil Immunotherapy. Issue 4 (May 2017) - Ghisoli, Maurizio; Rutledge, McCarley; Stephens, Philip J.; Mennel, Robert; Barve, Minal; Manley, Meghan; Oliai, Bahram R.; Murphy, Kathleen M.; Manning, Luisa; Gutierrez, Belen; Rangadass, Priyanka; Walker, Ashli; et al.
Abstract : Ewing sarcoma is a highly resistant disease with a <10% chance of survival at 5 years after failure of frontline chemotherapy. This is a case report of an Ewing sarcoma patient with metastatic disease recurrence <2 years after standard chemotherapy/radiation who achieved a durable and sustained complete response after 2 series of treatments with Vigil ( GMCSF/bi-shRNA furin DNA autologous tumor immunotherapy) serially manufactured from first and second recurrences with ELISPOT assay correlation. Results support justification of further testing of Vigil with ELISPOT assay as a biomarker to assess level of immune response and correlation with disease control.